DISCOURSE OF REFUGEES OPERATION SCHEME AFTER ISSUANCE OF PRESIDENTIAL DECREE NUMBER 125 OF 2016 ON THE TREATMENT OF FREIGN REFUGEES IN IMMIGRATION PERSPECTIVE - M. Alvi Syahrin; Bangun Widodo Pangestu (Polteknik Imigrasi, 2019)
As a state of law, Indonesia places legal norms as the fundamental foundation of the state. The issuance of Presidential Regulation No. 125 of 2016 on the Treatment of Foreign Refugees, has provided guidelines for Indonesia to deal with the existence of asylum seekers and refugees. The formulation of the problem studied is how the refugee control scheme after the issuance of Presidential Regulation No. 125 of 2016 in the immigration perspective. The research method uses normative legal research. The monitoring of refugees in Indonesia, which is imposed on the Immigration Detention Centre, has been well implemented. The monitoring scheme at the time it was found, at the shelter, outside the shelter, was dispatched to the destination country, voluntary repatriation, and at the time of deportation did not answer the problems related to the presence and activities of refugees while in Indonesia. Although the operation scheme has been clearly provided in Presidential Regulation No. 125 of 2016, it needs to be refined with technical regulations, such as the Standard Operating Procedure that regulates the mechanism of controlling refugees for all Immigration Detention Centre. Another issue of concern is the issue of funding, officials in charge of refugee control, and the imposition of sanctions if there is negligence in the case of such operation.